(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This study offers an evaluation of the economic background, financial systems, and market sizes of four key financial centres: New York, London, Tokyo, and Nigeria. These markets exhibit differing levels of development, global impact, and regulatory structures; each individually contributing to the global financial environment. New York is the biggest financial centre globally, characterised by substantial liquidity, market variety, and robust regulatory supervision. London’s financial system is distinguished by its long existence, global scope, convenient time zone, fintech advancements, and responsiveness to post-Brexit regulatory obstacles. Tokyo features a substantial domestic market characterised by a conservative investing ethos mixed with fintech drive whereas Nigeria exemplifies a developing market with growth prospects driven by its sizable population and fintech-oriented financial inclusion efforts. The research emphasizes critical elements like technological improvements, regulatory changes, and the influence of geopolitical concerns through a comparative examination of different financial systems. The text examines the dimensions and liquidity of each market, demonstrating the substantial variations in market capitalisation, trade volumes, and economic impact across different financial centres. The study concludes by delineating prospective trends that may transform these financial markets, encompassing the emergence of fintech, the integration of technology, and the changing role of retail investors. Among others, the study recommended that financial regulators across all four markets must persist in adapting and fortifying regulatory frameworks to mitigate growing risks, especially with technology and cryptocurrencies. Lucid and transparent laws will enhance investor trust and market stability.